ASSESSMENT OF RADON CONCENTRATION AND EXCESS LIFE CANCER RISK FOR WATER SAMPLES IN FEDERAL UNIVERSITY DUTSE (FUD), JIGAWA STATE, NIGERIA - Bello, Madaki; Dankawu, U. M.; Musa, I. M.; David Adamu, G. K.; Shuaibu, H. Y.; Mohammed, Yakubu; Zarma, S. S.; Abdullahi, Tahir; Zubairu, Nazifi; Shuaibu, Yusuf; Yakubu, A. (FUDMA JOURNAL OF SCIENCES, 2025)
Radon, a major cause of lung cancer, can be found in groundwater as it emanates from rocks and soil. The risk increases by 16% for every 100 Bq/m³ rise in long-term exposure. Even low radon levels, particularly from groundwater, pose health risks. The WHO estimates radon causes 3% to 14% of lung cancers, with risk rising proportionally to exposure. Six underground water samples (borehole) from within and outside FUD were analyzed using a Liquid Scintillation Counter at CERT in Zaria. Samples were collected from the Senate Building and student hostels. The mean radon concentration was 21.723 Bq/L, below the WHO (2017) and UNSCEAR (2020) limit of 100 Bq/L but above recommended levels of 10-11.1 Bq/L. Annual effective doses for inhalation and ingestion were 0.055, 0.161, 0.237, and 0.278 mSv/year for adults, children, and infants, with ingestion doses exceeding WHO limits. The cancer risk from ingestion exceeded the WHO standard of 2.9E-4, suggesting the water is not safe for drinking without treatment.